A study on contraction of pneumatic artificial muscle (pam) for load-lifting - Amanina Nadia Soaid (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Pneumatic Artificial Muscle (PAM) is a type of actuator that similar to human muscle. The PAM is used for converting pneumatic power to pulling force and enentually causing movements of mechanism. One of the potential usages of the PAM is load-lifting applications. In order to enhance the application of PAM, it is necessary to understand the basis of PAM development. But, only few numbers of study discuss the parameters and suitability of braided mesh with bladder that could enhance the PAM performance. To solve this problem, this study more focused on investigating the compatibility of braided mesh with bladder and also relationship of lenght and diameter bladder.